Pulsed laser deposition assisted epitaxial growth of cesium telluride photocathodes for high brightness electron sources - Kali Prasanna Mondal; Mengjia Gaowei; Elena Echeverria; Kenneth Evans-Lutterodt; Jean Jordan-Sweet; Thomas Juffmann; Siddharth Karkare; Jared Maxson; S. J. van der Molen; Chad Pennington; Pallavi Saha; John Smedley; et al. (Scientific Reports)
Abstract The development of high-brightness electron sources is critical to state-of-the-art electron accelerator applications like X-ray free electron laser (XFEL) and ultra-fast electron microscopy. Cesium telluride is chosen as the electron source material for multiple cutting-edge XFEL facilities worldwide. This manuscript presents the first demonstration of the growth of highly crystalized and epitaxial cesium telluride thin films on 4H-SiC and graphene/4H-SiC substrates with ultrasmooth film surfaces. The ordering of the film was characterized by in situ reflection high energy electron diffraction and multiple X-ray diagnostics. The results of the quantum efficiency performance for epitaxial cesium telluride photocathodes are also reported.